Does Delay Cause Decay? The Effect of Administrative Decision Time on the Labor Force Participation and Earnings of Disability Applicants - David Autor; Nicole Maestas; Kathleen Mullen; Alexander Strand (Institute for the Study of Labor (IZA), 2015)
This paper measures the causal effect of time out of the labor force on subsequent employment of Social Security Disability Insurance (SSDI) applicants and distinguishes it from the discouragement effect of receiving disability benefits. Using a unique Social Security Administration workload database to identify exogenous variation in decision times induced by differences in processing speed among disability examiners to whom applicants are randomly assigned, we find that longer processing times reduce the employment and earnings of SSDI applicants for multiple years following application, with the effects concentrated among applicants awarded benefits during their initial application. A one standard deviation (2.1 month) increase in initial processing time reduces long-run "substantial gainful activity" rates by 0.36 percentage points (3.5%) and long-run annual earnings by 178 (5.1%). Because applicants initially denied benefits spend on average more than 15 additional months appealing their denials, previous estimates of the benefit receipt effect are confounded with the effect of delays on subsequent employment. Accounting separately for these channels, we find that the receipt effect is at least 50% larger than previously estimated. Combining the delay and benefits receipt channels reveals that the SSDI application process reduces subsequent employment of applicants on the margin of award by twice as much as prior literature suggests.
Keywords: H53; I13; J22; J38; 330; disability; labor force participation; transfer programs; social security